Irish English: History and present-day forms - Hickey, Raymond (Cambridge University, 2013)
his book traces the development of English in Ireland, both north and south, from the late middle ages to the present day. Drawing on authentic data ranging from medieval literature to contemporary examples, it reveals how Irish English arose, how it has developed, and how it continues to change. A variety of central issues are considered in detail, such as the nature of language contact and the shift from Irish to English, the sociolinguistically motivated changes in present-day Dublin English, the special features of Ulster Scots, and the transportation of Irish English to overseas location as diverse as Canada, the United States and Australia. This book will be helpful for historical linguists, sociolinguists, syntacticians and phonologists alike.